SPEAKING STRATEGIES OF TAAPSEE PANNU: A PRAGMATIC ANALYSIS OF FILLER EXPRESSIONS - sari, septiana adela; Riyono2, Ahdi; Kurniati, Diah (LEAD (Language, Education and Development), 2025)
This study aims to identify the types and functions of filler expressions and to analyze their role as speaking strategies and pragmatic tools in Taapsee Pannu’s spontaneous speech. Using a qualitative descriptive approach, data were collected by documenting and observing a YouTube video of her speech. The analysis applied the classifications by Rose (1998) and Stenström (1994). The findings revealed a total of 143 filler expressions, consisting of 93 non-lexical fillers (such as “uh” and “um”) and 50 lexical fillers (such as “I mean,” “like,” and “you know”). These fillers performed five out of seven functions proposed by Stenström: hesitating, reformulating, initiating, linking, and emphasizing.To ensure the reliability of the analysis, an inter-rater test was conducted using the percentage agreement formula. The agreement between two raters reached 88.8% (127 agreements and 16 disagreements) for filler types, and 79.0% (113 agreements and 30 disagreements) for filler functions. These results indicate that the classification process was consistent and dependable. While non-lexical fillers occurred more frequently, lexical fillers were often used for more complex pragmatic purposes, including clarifying meaning and managing transitions. The study shows that filler expressions are not simply signs of disfluency, but they play important roles in maintaining fluency, organizing discourse, and creating a natural conversational flow. From a pragmatic viewpoint, fillers also reveal the speaker’s awareness, spontaneity, and ability to engage the audience effectively. These results highlight the communicative value of fillers in everyday spoken language.